The Impact Of The Work Environment On The Intention To Leave Work (A field study at Tishreen University): The Impact Of The Work Environment On The Intention To Leave Work (A field study at Tishreen University) (Journal of Hama University, 2022)
Abstract        This study aimed to clarify the impact of the work environment on the intention to leave work, and to achieve the goal of this study, the descriptive analytical method was relied on as a general approach to research. 315 questionnaires were distributed to faculty members at Tishreen University, and 263 questionnaires were retrieved, and the number of valid questionnaires for analysis was; 252 questionnaires. The data was analyzed by the statistical package for economic and social sciences. SPSS20). The most important results of the search were the following:The university does not provide transportation services for faculty members in an appropriate manner.The health care system does not adequately meet the needs of faculty members.There is an intention among the faculty members at Tishreen University to leave work.There is a significant impact of the material dimension of the work environment in the intention to leave work for faculty members at Tishreen University.There is a significant impact of the organizational dimension of the work environment on the intention to leave work for faculty members at Tishreen University.There is a significant impact of the work environment on the intention to leave work among the faculty members at Tishreen University.The researcher recommends that the university work to provide the basic requirements for the faculty member such as transportation, housing and health insurance services in an appropriate manner because of this important role in enabling the faculty member to perform the tasks assigned to him in an appropriate manner.
Keywords: Work; Environment; Intention; Leave